Establishment of fracture blister model and analysis of plasma protein markers in rats - Hu, Xin; Wang, Peiyuan; Wang, Tao; Cao, Jingcheng; Du, Kezheng; Scarlat, Marius M.; Liu, Lin; Li, Yutong; Wang, Xin; Wang, Haofei; Ma, Huijie; Wang, Ling; et al. (Frontiers in Immunology, 2025)
PurposeFracture blister (FB) is a frequent complication in orthopedic surgery. The primary objective of this study was to refine the animal model of FB and to identify plasma protein markers associated with its development and progression.MethodsIn this study, Sprague-Dawley (SD) rats were used as experimental subjects. Various pressures and compression durations were applied to the lower limbs of rats with fractures to compare the differential expression patterns (DEPs) between the pressure-time combination that resulted in the highest incidence of blisters and other groups. Subsequently, we investigated the variations in DEPs expression across different time intervals of the established model.ResultsOur findings indicate that following a lower limb fracture in SD rats, the highest incidence of blister formation was observed under conditions of 450 mmHg pressure and 9 hours of compression (46%, 7/15). In this group, the levels of CD44 and B2M were significantly elevated, while those of Activin R2A were reduced. Furthermore, we investigated the temporal profile of the group with the highest incidence of blister formation and found that CXCL16 and ROBO1 reached peak secretion 48 hours post-injury, followed by a subsequent decline. Additionally, the secretion of IL-2RG and IL-7 continued to increase 48 hours after the injury.Conclusionsthe increase of CD44 and B2M and the decrease of Activin R2A might be the potential influencing factors for the higher incidence of fracture blisters. CXCL16 and ROBO1 reached their peak 48 hours after the end of molding, and IL-2 RG and IL-7 R continued to increase 48 hours after the end of molding, which will provide a new direction for the study of the occurrence and development mechanism of fracture blisters.